Clinico-dermatoscopic and histopathological evaluation of cervico-facial hypermelanosis: a study from a tertiary care hospital - Simplepreet Kaur; Jasleen Kaur; Saurabh Sharma (Pigment International, 2020)
Introduction: Hypermelanosis is a rampant cosmetic problem nowadays. Unvarying and uniform skin color is the essence of vibrant skin. Hypermelanosis involving the face and neck is quite common and often becomes a challenge to the diagnostician. Persisting cervico-facial hypermelanosis causes cosmetic disfigurement which immediately sets one apart and consequently threatens psychosocial and psychosexual identity. Combining different modalities like dermatoscope and histopathology helps in early diagnosis and in time management of these disorders. Aims and Objectives: The data regarding the characterization of face and neck hyperpigmentation are scarce. This study was performed to determine the clinical types of face and neck hypermelanoses and establishment of their diagnosis using clinical, dermatoscopic, and histopathological features. Material and Methods: A total of 100 clinically diagnosed patients with hyperpigmentation over face and neck, in the age group of 18–70 years of either sex were enrolled in the study. Thorough clinical examination followed by dermatoscopic and histopathological examination were performed. All the features were noted and tabulated along with photographic documentation. Results: Out of total 100 cases, there were 35% cases of melasma, 23% cases of lichen planus pigmentosus, 12% cases of ashy dermatosis, 7% cases of post inflammatory hyperpigmentation, 6% cases of periorbital hypermelanosis, 4% cases of drug induced hyperpigmentation, 3% cases of acanthosis nigricans, nevus of ota, and macular amyloidosis each, 2% cases of riehl’s melanosis and exogenous ochronosis each. Conclusion: Hyperpigmentary disorders are great mimickers. Clinical examination alone can misdiagnose certain conditions. Dermatoscope, a novel office tool, when used along with time tested modality like histopathology, can reduce the diagnostic burden of clinicians while treating hyperpigmentary conditions.